A classification of EMG signal from masseter and buccinators, muscles to control the directional movement of power-assisted wheelchair - Al-Yasari, Hayder Abdulazeez Yousif (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2016)
The main objective of this research work is to control the movements of the wheelchair in five directions (forward, reverse, stop, left and right), using signals from the masseter and buccinator muscles as control signals. To achieve the main objective, the following sub-objectives are devised to design a method for acquiring the EMG signals based on masseter and buccinator muscle movements. To develop techniques and algorithms for extracting features from the EMG signals. To develop a classification algorithm using a K-nearest neighbor classifier and linear discriminant analysis. To develop a simple system for controlling a wheelchair using the EMG signals.